2010
DOI: 10.1128/mcb.00004-10
|View full text |Cite
|
Sign up to set email alerts
|

Doubles Game: Src-Stat3 versus p53-PTEN in Cellular Migration and Invasion

Abstract: We have recently shown that Src induces the formation of podosomes and cell invasion by suppressing endogenous p53, while enhanced p53 strongly represses the Src-induced invasive phenotype. However, the mechanism by which Src and p53 play antagonistic roles in cell invasion is unknown. Here we show that the Stat3 oncogene is a required downstream effector of Src in inducing podosome structures and related invasive phenotypes. Stat3 promotes Src phenotypes through the suppression of p53 and the p53-inducible pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 71 publications
(116 reference statements)
4
55
0
1
Order By: Relevance
“…We also observed a minor downregulation of STAT3 expression in TP53 +/+ cells. A similar observation was reported previously (31). When miR34a was specifically inhibited by an antagomir, the repression of IL-6R and STAT3 as well as the p53-mediated decrease in STAT3 phosphorylation was prevented ( Figure 4F and Supplemental Figure 5C), demonstrating that miR-34a mediates these effects of p53.…”
Section: Figuresupporting
confidence: 89%
“…We also observed a minor downregulation of STAT3 expression in TP53 +/+ cells. A similar observation was reported previously (31). When miR34a was specifically inhibited by an antagomir, the repression of IL-6R and STAT3 as well as the p53-mediated decrease in STAT3 phosphorylation was prevented ( Figure 4F and Supplemental Figure 5C), demonstrating that miR-34a mediates these effects of p53.…”
Section: Figuresupporting
confidence: 89%
“…Recent studies suggest that the effects of p53 on the processes of migration and invasion are cell context-dependent (Hollstein et al 1991, Vogelstein et al 2000, Lewis et al 2005, Moskovits et al 2006, Ku et al 2007, Morton et al 2008, Mukhopadhyay et al 2010. In line with our results, the accumulation of p53 protein in mouse embryonic fibroblasts has been revealed in the condition of forced expression of SOX2 (Li et al 2009, Banito andGil 2010).…”
Section: Discussionsupporting
confidence: 89%
“…It has been well established that PTEN may serve functions in a number of biological processes, including cell proliferation, the cell cycle, apoptosis, migration, invasion, metastasis, metabolism, differentiation, transcription and translation through negative regulation of the PI3K/AKT signaling pathway (38)(39)(40)(41)(42). Li et al (24) reported that in gastric cancer, PTEN expression is low in tumor tissues and was associated with advanced clinical stage and poor prognosis of patients with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%